2007
DOI: 10.1073/pnas.0707683104
|View full text |Cite
|
Sign up to set email alerts
|

Cold- and exercise-induced peak metabolic rates in tropical birds

Abstract: Compared with temperate birds, tropical birds have low reproductive rates, slow development as nestlings, and long lifespans. These ''slow'' life history traits are thought to be associated with reduced energy expenditure, or a slow ''pace of life.'' To test predictions from this hypothesis, we measured exercise-induced peak metabolic rates (PMRE) in 45 species of tropical lowland forest birds and compared these data with PMRE for three temperate species. We also compared cold-induced PMR (PMRC) with PMRE in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
123
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(134 citation statements)
references
References 71 publications
7
123
4
Order By: Relevance
“…Msum is generally lower in species from warmer tropical and subtropical environments compared to colder, temperate environments (Swanson and Garland 2009;Wiersma et al 2007a). Our finding that winter residual Msum is significantly higher among temperate-zone species compared to tropical/subtropical species is consistent with this overall picture, as is the corresponding difference in W/S ratios.…”
Section: Discussionsupporting
confidence: 81%
“…Msum is generally lower in species from warmer tropical and subtropical environments compared to colder, temperate environments (Swanson and Garland 2009;Wiersma et al 2007a). Our finding that winter residual Msum is significantly higher among temperate-zone species compared to tropical/subtropical species is consistent with this overall picture, as is the corresponding difference in W/S ratios.…”
Section: Discussionsupporting
confidence: 81%
“…Tropical birds have a significantly lower basal and peak metabolic rate than temperate birds (Wiersma et al, 2007a;Wiersma et al, 2007b), which may translate into a higher production of damaging free radicals, because ROS production is highest when respiration rate is low. However, because tropical birds have high rates of survival (Ricklefs, 1997;Tieleman et al, 2006), they may have evolved efficient cellular mechanisms to regulate ROS-induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of a linkage between slow pace of life and low rate of metabolism in tropical birds came to light when it was shown that they had a significantly lower wholeanimal basal metabolic rate (Wiersma et al, 2007a) and peak metabolic rate as measured by cold-exposure or by exercise (Wiersma et al, 2007b). Later it was discovered that a contributing factor to the reduced rate of metabolism in tropical birds was their smaller metabolically active organs, such as the heart, liver, kidneys and pectoral muscles, compared with similar-sized temperate species (Wiersma et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Given that tropical birds have smaller clutches, longer parental care, and higher juvenile and adult survival than their north-temperate counterparts [Moreau 1944;Skutch 1985;Martin 1996;Cardillo 2002;Russell et al 2004)], these studies support the notion that a slow 'pace of life' engenders a slow 'pace' of energy metabolism (e.g., Pearl 1928). However, it is unclear if low BMR in the tropics is a functional necessity or a byproduct of 'slow' life history, or instead is simply an outcome of living in warm, stable habitats with low requirements for thermoregulation, migration, or other energetically demanding activities (Wiersma et al 2007a). One way to resolve this is to examine the metabolic rates of temperate-breeding birds sharing the same 'slow' life-history traits as tropical passerines, and compare them with sympatric passerines with 'fast' life-histories.…”
Section: Introductionmentioning
confidence: 99%
“…Adults from a sedentary tropical population had lower metabolic rates than birds from a migratory north-temperate population. Similarly, two extensive comparative analyses showed that birds from Neotropical forests in Panama and Peru have lower BMR (Wiersma et al 2007b;Londoño et al 2015) and, in the Panamanian birds, lower maximal metabolic rates than species from temperate latitudes (Wiersma et al 2007a). Given that tropical birds have smaller clutches, longer parental care, and higher juvenile and adult survival than their north-temperate counterparts [Moreau 1944;Skutch 1985;Martin 1996;Cardillo 2002;Russell et al 2004)], these studies support the notion that a slow 'pace of life' engenders a slow 'pace' of energy metabolism (e.g., Pearl 1928).…”
Section: Introductionmentioning
confidence: 99%